Assessment of Beddown Alternatives for the F-35 - McGarvey, Ronald G. (RAND Corporation, 2013)
The F-35 Joint Strike Fighter is the most costly aircraft acquisition program in Defense Department history. RAND assessed the potential for savings by reconfiguring the U.S. Air Force's combat-coded F-35s into larger squadrons, adjusting the Primary Aerospace Vehicle Authorized (PAA) mix across the Active and Reserve Components, and adjusting the percentage of PAA permanently assigned to locations in the continental United States.